1988
DOI: 10.1016/s0046-8177(88)80201-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic spermatozoa

Abstract: Spermatozoa have not previously been described within the prostate gland. Nine of one hundred prostates of nonhospitalized males obtained from autopsy during the course of medicolegal death investigation were found to contain spermatozoa. The potential role of spermatozoa in the pathogenesis of corpora amylacea/calculi formation, granulomatous inflammation, local antigenic stimulation, and carcinogenesis is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Other authors have reported similar findings and suggested that the allergic component was a protein(s) in the range of 20-40 KD [12,13]. An antigen does not need to be produced by the prostate for the prostate to be affected as intraprostatic spermatozoa have been found on postmortem analysis [14] mainly in the peripheral zone.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Other authors have reported similar findings and suggested that the allergic component was a protein(s) in the range of 20-40 KD [12,13]. An antigen does not need to be produced by the prostate for the prostate to be affected as intraprostatic spermatozoa have been found on postmortem analysis [14] mainly in the peripheral zone.…”
Section: Introductionmentioning
confidence: 53%
“…Other authors have reported similar findings and suggested that the allergic component was a protein(s) in the range of 20-40 KD [12,13]. An antigen does not need to be produced by the prostate for the prostate to be affected as intraprostatic spermatozoa have been found on postmortem analysis [14] mainly in the peripheral zone.The finding of increased levels of IgA and IgG in the expressed prostatic secretion of patients with abacterial prostatitis, compared to controls, supports an autoimmune aetiology for this condition, since this Ig was not specific for known microorganisms …”
mentioning
confidence: 53%
See 1 more Smart Citation
“…By phagocytosis, prostate macrophages can remove refluxed urethral material and spermatozoa. Such a mechanism can be relevant, since in the prostate, spermatozoa have been shown to induce prostatitis, abscesses, and lithiasis, and are thought to be responsible, as in other tissues of the male reproductive tract, for granuloma reaction [29]. In addition, by removing degenerated epithelial cells, incorporated together with spermatozoa in the corpora amylacea, macrophages prevent one of the possible mechanisms of obstruction of the glandular ducts.…”
Section: Discussionmentioning
confidence: 99%
“…The physical contact between luminal and stromal cells augments the expression of stromal MMP, facilitating epithelial-mesenchymal transition (EMT) and cell motility [58][59][60]. e. The physical contact between luminal and immunoreactive cells directly cause genomic or cellular damages that trigger a cascade reaction of malignant transformation [61][62][63][64]. 8.…”
Section: The Hypothesized Main Steps Of Tumor Invasionmentioning
confidence: 99%